2017
DOI: 10.5941/myco.2017.45.4.312
|View full text |Cite
|
Sign up to set email alerts
|

Differences among Endophytic Fungal Communities Isolated from the Roots ofCephalanthera longibracteataCollected from Different Sites in Korea

Abstract: Orchidaceous plants have symbiotic relationships with endophytic fungi, including mycorrhizal fungi, which play important roles in the seed germination and growth of the host plants. In this study, endophytic fungal communities isolated from the roots of Cephalanthera longibracteata collected from three different sites in Korea were analyzed, and it was determined whether fungal communities were preferentially correlated with the sites. The fungal isolates were identified by sequence analysis of the internal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…11,14 The in vitro culture of selected samples on different growth medium showed that the diversity of endophytic fungi was found higher in PDA than the Czapek's medium might be the suitable range of pH and nutrients conditions in the PDA medium. 14,15 Fungal diversity and richness of this study was slightly differed than previous studies which might be due to the differences in environmental conditions, the climatic factor of orchid's habitat as well as differences in culture medium and conditions of laboratories among the different researches. Whereas, Fusarium, Alternaria species were dominant in overall isolated endophytic fungi.…”
Section: Discussioncontrasting
confidence: 64%
“…11,14 The in vitro culture of selected samples on different growth medium showed that the diversity of endophytic fungi was found higher in PDA than the Czapek's medium might be the suitable range of pH and nutrients conditions in the PDA medium. 14,15 Fungal diversity and richness of this study was slightly differed than previous studies which might be due to the differences in environmental conditions, the climatic factor of orchid's habitat as well as differences in culture medium and conditions of laboratories among the different researches. Whereas, Fusarium, Alternaria species were dominant in overall isolated endophytic fungi.…”
Section: Discussioncontrasting
confidence: 64%
“…Most vulnerable orchids have inhabitants of <100 plants and their management is one of the key encounters faced by cultivators [6]. Determining influences disturbing the spatial dispersal and richness of endangered Orchidaceae plants is a chief encounter in existing protection biology [7]. Endophytes have shown a synergetic cooperation of fungus with their Orchidaceae family [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that rapid growth of certain fungal species may suppress other slow-growing ones sharing the same niche. SITE SPECIFICITY Lee et al (2017) reported that species diversity and richness of endophytic fungi colonizing the roots of Cephalanthera longibracteata were not significantly different between sites. However, the community structure of the endophytic fungi did significantly differ between sites, suggesting that site characteristics affected the community composition of those endophytic fungi.…”
Section: Seasonal Effect On the Fungal Communitymentioning
confidence: 99%